PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN KREATIVITAS DAN KETERAMPILAN BERBICARA ANAK KELOMPOK B DI PAUD RA. KARTINI PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Lisna Ningsih; Nina Kurniah (DIADIK, 2022)
The research objective was to describe the application of the role playing method to improve the creativity and speaking skills of group B children in PAUD RA. Kartini Pondok Kelapa, Central Bengkulu Regency. The type of research used is Classroom Action Research (PTK). Research subjects at the PTK were 15 children of group B PAUD RA. Kartini Pondok Kelapa, Central Bengkulu Regency. The data collection technique used was observation. The PTK data analysis technique used the average value formula, for the PTK data analysis the significance t-test was used. Based on the results of the study, it can be concluded that the application of the role playing method can significantly improve children's creativity and speaking skills. Therefore the teacher can apply the role playing method by using an attractive classroom setting so as to create fun learning activities in role playing.